2016
DOI: 10.1038/am.2016.157
|View full text |Cite
|
Sign up to set email alerts
|

Monolayer 1T-NbSe2 as a Mott insulator

Abstract: The emergence of exotic quantum phenomena is often triggered by a subtle change in the crystal phase. Transition metal dichalcogenides (TMDs) exhibit a wide variety of novel properties, depending on their crystal phases, which can be trigonal prismatic (2H) or octahedral (1T). Bulk NbSe 2 crystallizes into the 2H phase, and the charge density wave and the superconductivity emerge simultaneously and interact with each other, thereby creating various anomalous properties. However, these properties and their inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

21
125
4
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 129 publications
(155 citation statements)
references
References 36 publications
(55 reference statements)
21
125
4
1
Order By: Relevance
“…After evaporating V atoms in Se atmosphere onto the substrate kept at 400 ºC, the RHEED intensity due to graphene and buffer structure is reduced, and instead a new sharp 1×1 streak pattern appears ( Fig. 1(c)) similarly to the case of other monolayer TMD films on bilayer graphene [4,20,21], indicating the formation of monolayer VSe2 on bilayer graphene. As seen in the ex-situ AFM image ( Fig.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…After evaporating V atoms in Se atmosphere onto the substrate kept at 400 ºC, the RHEED intensity due to graphene and buffer structure is reduced, and instead a new sharp 1×1 streak pattern appears ( Fig. 1(c)) similarly to the case of other monolayer TMD films on bilayer graphene [4,20,21], indicating the formation of monolayer VSe2 on bilayer graphene. As seen in the ex-situ AFM image ( Fig.…”
Section: Resultsmentioning
confidence: 91%
“…Figure 1(b) shows the reflection high-energy electron diffraction (RHEED) pattern of pristine bilayer graphene grown on 6H-SiC(0001). We clearly observe the 1×1 streak pattern and the 6√3×6√3R30° spots originating from bilayer graphene and underlying buffer structure, respectively [4,20,21]. After evaporating V atoms in Se atmosphere onto the substrate kept at 400 ºC, the RHEED intensity due to graphene and buffer structure is reduced, and instead a new sharp 1×1 streak pattern appears ( Fig.…”
Section: Resultsmentioning
confidence: 93%
“…Lack of inversion symmetry and van der Waals bonded layers may result in remarkably different behavior with respect to the bulk [39][40][41]. The 2H-1T crystal phase transition at the surface of NbSe 2 [42,43] (the 1T crystal phase is unstable in the bulk [44]), the occurrence of 4 × 4 [3,4] and/or a 2 × 2 [4] modulations, linked to a stripe phase, and the observation of distinct charge density wave structures, determining a factor for the incommensuration character [6], are just a few recent examples. A change from the 3×3 to the 4×4 modulation was previously predicted by ab-initio studies [20,48]; on the other hand, a recent study [5] showed that within a 3 × 3 modulation, uniaxial strain leads to a trigonal-stripe CDW stransition.…”
mentioning
confidence: 99%
“…As a similar technique has been used for the synthesis of 1T-NbSe 2 (with a different substrate) in Ref. 11 , this makes the synthesis of single layer 1T-NbS 2 even more likely.…”
Section: Resultsmentioning
confidence: 99%